2015
DOI: 10.1093/toxsci/kfv044
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Morphological — Behavioral Test Platform Reveals Neurodevelopmental Defects in Embryonic Zebrafish Exposed to Comprehensive Suite of Halogenated and Organophosphate Flame Retardants

Abstract: The increased use of flammable plastics and electronic devices along with stricter fire safety standards has led to the heavy use of flame retardant chemicals in many consumer, commercial, and industrial products. Although flame retardant use has increased, a great deal of uncertainty surrounds their safety with some evidence showing toxicity and risk to human and environmental health. Recent efforts have focused on designing high-throughput biological platforms with nonmammalian models to evaluate and priorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
162
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(192 citation statements)
references
References 74 publications
18
162
5
Order By: Relevance
“…Instead, it was found that exposures an order of magnitude higher decreased larval activity in both the light and dark (Dishaw et al, 2014). Another study also failed to find that TPHP exposure during the same time period produced behavioral effects up to a dose two orders of magnitudes higher, at which point TPHP also depressed locomotion (Noyes et al, 2015). The same study, however, found that TDCIPP increased locomotion at doses near the higher dose tested here, but attenuated it at higher doses (Noyes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, it was found that exposures an order of magnitude higher decreased larval activity in both the light and dark (Dishaw et al, 2014). Another study also failed to find that TPHP exposure during the same time period produced behavioral effects up to a dose two orders of magnitudes higher, at which point TPHP also depressed locomotion (Noyes et al, 2015). The same study, however, found that TDCIPP increased locomotion at doses near the higher dose tested here, but attenuated it at higher doses (Noyes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also failed to find that TPHP exposure during the same time period produced behavioral effects up to a dose two orders of magnitudes higher, at which point TPHP also depressed locomotion (Noyes et al, 2015). The same study, however, found that TDCIPP increased locomotion at doses near the higher dose tested here, but attenuated it at higher doses (Noyes et al, 2015). Variations between these results may partially be explained by differences in testing protocol (eg, beginning with a light phase as opposed to a dark phase) or differences in strain of zebrafish (5D in both Dishaw et al, 2014 and Noyes et al, 2015 compared to the AB* strain used here).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the critical processes of zebrafish neurodevelopment are homologous to those in humans [14]. Neuronal effects of developmental chemical exposure on embryo and larval photomotor activity can be easily measured in zebrafish, widening the potential field of bioactivity that can be detected [15, 16]. It was found that developmental mortality/morphology endpoints, combined with the larval photomotor response, serve as a robust biological sensor for chemical hazard potential.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some halogenated OPEs, such as tris(2-chloroethyl)phosphate (TCEP), tris(chloroisopropyl)phosphate (TCPP) and tris(1,3-dichloro-2-propyl)phosphate (TDCP), are quite recalcitrant to naturally degradation or biodegradation [1,3], suggesting that they are likely to enter the aquatic environment and persistent in environment. In addition, extensive studies have showed that exposure to several OPEs pose a potential health risk for animals and humans [12][13][14].…”
Section: Introductionmentioning
confidence: 99%